The Social Determinants of Health in Association with Women's Health Status of Reproductive Age: A Population-Based Study - Azam Baheiraei; Fatemeh Bakouei; Eesa Mohammadi; Ali Montazeri; Mostafa Hosseni (Tehran University of Medical Sciences, 2015)
Background: Prioritizing women's health helps achievement of the 4th and 5th goals of Millennium Development  Program. This study aimed to investigate association between social determinants of health and women's health of reproductive age. Methods: This population-based cross-sectional study, using multi-stage sampling procedure was conducted on 770,  15 to 49-year-old women residing in any one of the 22 municipality zones across Tehran, Iran. Eligible women were  interviewed at home with SF-36 (Short Form Health Survey) and socio-demographic questionnaires. Social determinants of health contains; ethnicity, education, job, income, and crowding index. Data were analyzed by ANOVA and Multiple Linear Regression using SPSS-16.The threshold of P.V was considered 0.05. Results: Overall, 770 women with mean age 33.9±9.3 years were interviewed. Majority of them were married (72.27%),  housewives (62.2%), of Persian ethnicity (64.3%), and educated to high school level (43.8%). Age with dimensions of health except role emotional, mental health, and social functioning had significant association with B from -0.65 to -0.16.educational level with dimensions of health except role emotional andsocial functioning had significant association with B from 3.61 to 6.43 (P<0.05). Income with dimensions of health except role physical had significant association with B from -9.97 to -4.42. Conclusion: Reflection of unfavorable economic conditions and low education level on negative women' health experiences are alarming. Interaction between social determinants of health and health status must be considered in policymaking, and there is a need for policies that would enhance health of women in the low education and income brackets.